Specifics in the provision of integrated services in the conditions of convergence of IoT (Internet of Things) and AI (Artificial Intelligence) technologies - Simeonova, Tsvetelina (Yearbook Telecommunications, 2024)
The aim of the work is to research the specifics of the provision of integrated services in the conditions of convergence of Internet of Things (IoT) and Artificial Intelligence (AI) technologies. Results have been obtained related to highlighting the features of AI-based IoT services, as well as the specificity of machine learning technologies in the provision of IoT services. Clarifying the specifics of real-time simplified intelligence technologies and federated learning stand out as contributing moments.